2013
DOI: 10.1371/journal.pone.0055495
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing in DR Congo: A Knowledge, Attitude and Practice Survey among Medical Doctors and Students

Abstract: ObjectivesAntibiotic resistance (ABR) particularly hits resource poor countries, and is fuelled by irrational antibiotic (AB) prescribing. We surveyed knowledge, attitudes and practices of AB prescribing among medical students and doctors in Kisangani, DR Congo.MethodsSelf-administered questionnaires.ResultsA total of 184 questionnaires were completed (response rate 94.4%). Knowledge about AB was low (mean score 4.9/8 points), as was the estimation of local resistance rates of S. Typhi and Klebsiella spp.(corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
214
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(255 citation statements)
references
References 17 publications
31
214
10
Order By: Relevance
“…The median number of students per study was 104 (range 1–2413). Besides final‐year medical students, some studies also involved 1–5th year students ( n = 20) 24, 25, 26, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, junior doctors and residents ( n = 8) 25, 28, 33, 46, 47, 48, 49, 50, medical specialists ( n = 2) 48, 50, pharmacy students ( n = 3) 32, 51, 52, dental students ( n = 2) 31, 41 and nonhealthcare students ( n = 1) 40.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median number of students per study was 104 (range 1–2413). Besides final‐year medical students, some studies also involved 1–5th year students ( n = 20) 24, 25, 26, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, junior doctors and residents ( n = 8) 25, 28, 33, 46, 47, 48, 49, 50, medical specialists ( n = 2) 48, 50, pharmacy students ( n = 3) 32, 51, 52, dental students ( n = 2) 31, 41 and nonhealthcare students ( n = 1) 40.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles evaluated students' attitudes to, and knowledge of, appropriate antimicrobial prescribing and resistance 23, 24, 35, 36, 37, 39, 40, 44, 48, 49, 52, 76, 77, 78, 79. Students generally had positive attitudes and perceptions about antimicrobial overuse and resistance 35, 49, 76, 77.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study in the Northeast of the United States, medical students emphasized the need for both education and feedback on antimicrobial prescribing in order to control overuse or misuse which was high among the population in general [11]. In addition, it was reported that University students misuse antibiotic [12,13]. Furthermore, in China the widespread prescribing of unnecessary antibiotics, especially antibiotics administered parentally [12].…”
Section: Introductionmentioning
confidence: 99%